Моделювання споживання електричної енергії динамічним навантаженням в електричних мережах промислових підприємств - Романовський, В. І.; Іванов, О. О. (НТУ "ХПІ", 2014)
Запропоновано метод моделювання процесу роботи обладнання з динамічним характером споживання електричної енергії в електричних мережах промислових підприємств. Застосування теорії миттєвої потужності дозволяє оцінити вплив режиму роботи таких споживачів на мережу в цілому та на суміжних споживачів. Виконано моделювання роботи обладнання у цеху промислового підприємства, що дозволило підвищити ефективність споживання електричної енергії.

The paper proposes a method for modeling the work process of equipment with the dynamic nature of power consumption in power networks in industry. The method is based on the definition of instantaneous active and reactive power, and instantaneous fluctuating active and reactive power, determined using the mathematical apparatus of the theory of instantaneous power. Application of the theory of instantaneous power allows to estimate the impact of the operating mode of the network of consumers in general and related customers. If mode of operation of the equipment with the dynamic nature of electricity consumption was changed, fluctuations appear. Simulation of plant equipment in an industrial enterprise, thus improving the efficiency of power consumption.
Simulation of consumption the electric energy by dynamic loads in electrical networks of industrial enterprises
Keywords: енергоефективність; миттєва потужність; ефективна потужність; математичне моделювання; energy efficiency; instantaneous power; effective power; dynamic load; mathematical modeling